Crack/cocaine users show more family problems than other substance users (Clinics, 2014)
OBJECTIVES: To evaluate family problems among crack/cocaine users compared with alcohol and other substance users. METHODS: A cross-sectional multi-center study selected 741 current adult substance users from outpatient and inpatient Brazilian specialized clinics. Subjects were evaluated with the sixth version of the Addiction Severity Index, and 293 crack users were compared with 126 cocaine snorters and 322 alcohol and other drug users. RESULTS: Cocaine users showed more family problems when compared with other drug users, with no significant difference between routes of administration. These problems included arguing (crack 66.5%, powder cocaine 63.3%, other drugs 50.3%, p = 0.004), having trouble getting along with partners (61.5%×64.6%×48.7%, p = 0.013), and the need for additional childcare services in order to attend treatment (13.3%×10.3%×5.1%, p = 0.002). Additionally, the majority of crack/cocaine users had spent time with relatives in the last month (84.6%×86.5%×76.6%, p = 0.011). CONCLUSIONS: Brazilian treatment programs should enhance family treatment strategies, and childcare services need to be included.